Influenza Vaccine Effectiveness in Preventing Hospitalizations in Older Patients With Chronic Obstructive Pulmonary Disease. (24th September 2019) - Gershon, Andrea S; Chung, Hannah; Porter, Joan; Campitelli, Michael A; Buchan, Sarah A; Schwartz, Kevin L; Crowcroft, Natasha S; Campigotto, Aaron; Gubbay, Jonathan B; Karnauchow, Timothy; Katz, Kevin; McGeer, Allison J; et al.
Abstract: Background: Annual influenza immunization is recommended for people with chronic obstructive pulmonary disease (COPD) by all major COPD clinical practice guidelines. We sought to determine the seasonal influenza vaccine effectiveness (VE) against laboratory-confirmed influenza-associated hospitalizations among older adults with COPD. Methods: We conducted a test-negative study of influenza VE in community-dwelling older adults with COPD in Ontario, Canada using health administrative data and respiratory specimens collected from patients tested for influenza during the 2010–11 to 2015–16 influenza seasons. Influenza vaccination was ascertained from physician and pharmacist billing claims. Multivariable logistic regression was used to estimate the adjusted odds ratio of influenza vaccination in people with, compared to those without, laboratory-confirmed influenza. Results: Receipt of seasonal influenza vaccine was associated with an adjusted 22% (95% confidence interval [CI], 15%–27%) reduction in laboratory-confirmed influenza-associated hospitalization. Adjustment for potential misclassification of vaccination status increased this to 43% (95% CI, 35%–52%). Vaccine effectiveness was not found to vary by patient- or influenza-related variables. Conclusions: During the studied influenza seasons, influenza vaccination was at least modestly effective in reducing laboratory-confirmed influenza-associated hospitalizations in people with COPD. The imperfect effectiveness emphasizes the need for better influenza vaccines and other preventive strategies. Abstract : Influenza vaccination is modestly effective in reducing laboratoryconfirmed influenza-associated hospitalizations in people with COPD.